Prenatal detection of 10q22q23 duplications: dilemmas in phenotype prediction. (29th November 2016) - Kong, Grace Wing Shan; Cao, Ye; Huang, Jin; Cheng, Kwun Yue; Pursley, Amber Nolen; Rosenfeld, Jill Anne; Edwards, Janice G.; Chan, Yiu Man; Cheung, Sau Wai; Leung, Tak Yeung; Choy, Kwong Wai
Abstract: Objectives: The phenotype for 10q22q23 duplication is diverse, ranging from intellectual disability and dysmorphism to normal development. Interpreting the clinical significance of the duplication identified in this region is difficult, especially in the prenatal setting. This study aimed to characterize the prenatal findings associated with this submicroscopic imbalance and discuss the dilemmas in predicting the phenotype of 10q22q23 duplications. Methods: This is a retrospective study of three cases of 10q22q23 duplications diagnosed prenatally by chromosomal microarray analysis. Detailed pregnancy outcome and pediatric follow‐up were documented. Results: The genotypic and phenotypic features of the reported cases were discussed. 10q22q23 duplications are associated with an unpredictable and variable phenotypic outcome. Despite there was no phenotype found to be shared by 50% of the duplication cases, congenital heart defects, hypotelorism, and developmental delays including speech and motor delay seem to be more common. Conclusions: The phenotype of 10q22q23 duplication is highly variable prenatally and postnatally. Identification of additional affected individuals with similar duplications is needed to provide further insights into the pathogenesis of this microduplication. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Chromosomal region 10q22q23 is characterized by a complex set of low‐copy repeats, which are hotspots for unequal crossovers leading to deletions and duplications. Postnatal phenotype for 10q22q23 duplication is diverse. What does this study add? Similar to the postnatal cases, prenatally detected 10q22q23 duplications are associated with a variable phenotypic outcome on ultrasound assessment. If congenital heart defects and hypotelorism are identified prenatally, the submicroscopic chromosomal imbalance with 10q22q23 duplication could be considered.